2013
DOI: 10.1021/ol400432x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidative 1,2-Shift in 1,1′-Disubstituted Olefins Using Arene(iodo)sulfonic Acid as the Precatalyst and Oxone as the Oxidant

Abstract: An efficient, catalytic hypervalent iodine-mediated oxidative 1,2-shift of 1,1'-disubstituted olefins is described. This methodology provides concise access to homobenzylic ketones with electron-donating substituents. In the case of cyclic systems, this transformation results in ring-expanded β-benzocycloalkanones, which are useful for further elaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…The employment of catalytic amounts of iodine reagent in combination with an external oxidant for hypervalent iodine‐mediated transformations is an active area of research . It has been shown that electron‐rich 1‐alkyl‐1‐arylethenes can rearrange to ketones with sub‐stoichiometric quantities of 4‐methyl‐iodobenzenesulfonic acid . We found that more electron‐rich 1,1‐diarylalkenes, such as 6 a , suffered from direct reaction with the terminal oxidants in preference to the iodine(I)→iodine(III) oxidation of chiral iodoarenes.…”
Section: Resultsmentioning
confidence: 81%
“…The employment of catalytic amounts of iodine reagent in combination with an external oxidant for hypervalent iodine‐mediated transformations is an active area of research . It has been shown that electron‐rich 1‐alkyl‐1‐arylethenes can rearrange to ketones with sub‐stoichiometric quantities of 4‐methyl‐iodobenzenesulfonic acid . We found that more electron‐rich 1,1‐diarylalkenes, such as 6 a , suffered from direct reaction with the terminal oxidants in preference to the iodine(I)→iodine(III) oxidation of chiral iodoarenes.…”
Section: Resultsmentioning
confidence: 81%
“…Inspired by the pioneering work of Koser et al. on the hypervalent iodine‐promoted ketone synthesis that involves bond rearrangement, Purohit and co‐workers developed rearrangement‐based oxygenation reactions of terminal alkenes 73 for the synthesis of ketone products 74 through iodine(III) catalysis. In this procedure, iodobenzenesulfonic acid 75 was employed as precatalyst that was transformed into iodine(III) catalyst 76 in the presence of the terminal oxidant oxone.…”
Section: Carbonyl Formation By Oxygenation Based On Partial Cleavagementioning
confidence: 99%
“…When treated with a sub-stoichiometric amount of 2-iodo-5-methylbenzenesulfonic acid 55 as a pre-catalyst and in the presence of Oxone® as a co-oxidant, olefin 54 is transformed into the corresponding ketone 56 as shown in Scheme 17 [13]. It should be stressed that those conditions imply only 80 mol% of Oxone®, in order to generate a reactive iodine species(III) and not to overoxidize the reagent into an iodine(V), which would probably be unable to promote the desired transformation.…”
Section: Racemic Pathwaymentioning
confidence: 99%